The Implementation of Character Education in Teaching English as a Foreign Language in SMA Cendana Pekanbaru - Ariyanto, Joko; Rugaiyah, Rugaiyah; Roziah, Roziah; Yulianto, Yulianto; Irenta, Astrid (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Character education has been widely promoted in Indonesian education policy; however, empirical studies examining how it is enacted in EFL classrooms at the senior high school level remain limited, particularly in terms of classroom-level practices and teacher interpretation. This qualitative case study investigates the implementation of character education in EFL teaching at SMA Cendana Pekanbaru, focusing on how values are enacted in practice. Data were collected from two English teachers through lesson plan analysis (n=12), classroom observations (n=6 sessions), and semi-structured interviews. The findings reveal that character education is primarily integrated through (1) routine-based classroom management practices that reinforce discipline and responsibility, (2) teacher modelling and interactional feedback that promote respect and honesty, and (3) task-based activities that implicitly embed cooperation and perseverance. However, implementation remains surface-level, as teachers prioritize linguistic targets and rarely engage students in critical moral reflection. Given the small-scale, bounded nature of the study, the findings highlight how policy-level expectations are selectively enacted in classroom practice rather than fully realized. The study underscores the need for pedagogical support that moves beyond implicit integration toward more reflective and explicit character education in EFL contexts.